The WISEWOMAN Program: Reflection and Forecast - Will, Julie C (Centers for Disease Control and Prevention, 2008)
The WISEWOMAN program targets low-income under- and uninsured women aged 40–64 years for screening and interventions aimed at reducing the risk of heart disease, stroke, and other chronic diseases. The program enters its third phase on June 30, 2008. Design issues and results from Phase I and Phase II have been published in a series of papers. We summarize remaining challenges, which were identified through systematic research and evaluation. Phase III will address these challenges through a number of new initiatives such as allowing interventions of different intensities, taking advantage of resources for promoting community health, and providing evidence-based interventions through the program's Center of Excellence. Finally, we provide a framework and vision so that organizational, community, and other partners can make the case for the importance of the program to their communities and for what is needed to make it work.